Comparison of Serum Luteinizing Hormone, Follicle-Stimulating Hormone and Testosterone in Healthy Women and Polycystic Ovarian Syndrome Patients (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Polycystic Ovarian Syndrome (PCOS) is the most frequent endocrinopathy among young women. PCOS causes menstrual dysfunction, infertility, hirsutism, acne, obesity, and hormonal imbalance. The study will evaluate LH, FSH, and Testosterone levels in polycystic ovarian syndrome patients and healthy Chattogram women.  Materials and methods: This cross-sectional comparative study was conducted in Chittagong Medical College Hospital's Biochemistry and Gynaecology and Obstetrics Departments from July 2016 to June 2017. Purposive sampling chose hundred (100) 20-35-year-old women who met enrollment criteria. In addition to 50 polycystic ovarian syndrome patients, 50 healthy reproductive females were present. Both case and control had been tested serum FSH, LH and Testosterone levels.  Results: The average age of patients with Polycystic Ovary Syndrome (PCOS) was 30.6±0.65 years. In this study, 54% of the patients had obesity, 92% had oligomenorrhea, 8% had amenorrhoea and 22% had hirsutism. There were notable disparities in the blood LH and testosterone levels between the cases and controls. In addition, the serum FSH level was lower in the patients compared to the control group. However, the differences in serum FSH levels between the cases and controls did not reach statistical significance.  Conclusions: Polycystic Ovarian Syndrome (PCOS) is the predominant kind of persistent an ovulation that is linked to excessive levels of androgens. Regular monitoring and timely control of serum androgen levels would be highly beneficial in preventing problems associated with PCOS.JCMCTA 2024 ; 35 (2) : 72-76